The Meaning of Sign in Public Service Advertisement: The Meaning of Sign in Public Service Advertisement - Mareta, Ni Putu Dita; Beratha, Ni Luh Sutjiati; Savitri, Putu Wedda (Program Studi Sastra Inggris, Fakultas Ilmu Budaya, Universitas Komputer Indonesia, 2025)
This research entitled “The Meaning of Signs in Public Service Advertisement”. The aims to find the verbal and visual signs in the United Nation International Children Emergency Fund’s public service advertisement and explain the meaning of signs in the advertisement. The data was taken from website. The discussion of this study was about the verbal and visual signs that found in UNICEF advertisement and explain the meaning of those signs. The theory of Semiotics by Saussure (citied in Chandler) is used to find out the verbal and visual signs that found in advertisement. And the theory from Barthes is used to explain the meaning of verbal and visual signs in advertisement. And supported by the theory of colour meaning by Cerrato. Four verbal and visual cues from UNICEF's advertising are included in the analysis's output. Both denotative and connotative meanings are included in these verbal and visual cues; the former concentrates on providing readers with information about the advertisement, while the latter focuses on revealing additional meanings and hidden messages from the commercial. Keywords: Verbal Sign, Visual Sign, Public Service Advertisement